An effective engineering computational procedure to analyse and design rotary regenerators using a porous media approach. (April 2016) - Alhusseny, Ahmed; Turan, Ali
Highlights: A less expensive way than experiments is presented to design rotary regenerators. Porous media approach is sufficient to accurately simulate rotating heat exchangers. Core geometrical characteristics have a direct impact on the overall performance. Carryover loss increases with rotation increase or decreasing the mass flow rate. Pressure drop must be minimised while trying to enhance the effectiveness attained. Abstract: A numerical analysis of the fluid flow and heat transport phenomenon through a rotary thermal regenerator is presented using a porous media approach. An aluminium core formed of multi packed passages is simulated as a porous medium of orthotropic porosity in order to allow the counter-flowing streams to flow in a way similar to that inside the regenerator core. Based on empirical equations, geometric properties of the core were transformed into the conventional porous media parameters such as the permeability and inertial coefficient; so, the core has been dealt with as a porous medium of known features. Heat is only allowed to transport within the rotating core, where a local thermal non-equilibrium situation is assumed there between the fluid and solid phases. The use of porous media approach has been found to be sufficient to solve the current problem. The results are presented by means of overall regenerator effectiveness, pressure drop, and the overall system performance. The impact of different design aspects were investigated such as the core geometrical characteristics, core dimensions, and operating conditions. The data obtained reveal an obvious impact of the parameters inspected on both the heat restored and the pressure loss; and hence, the overall efficiency of the regenerator system. Although regenerator effectiveness can be improved considerably by manipulating the design factors, care must be taken to avoid unjustified expenses resulted from potential augmentation in pressure drop.